CONCENTRAÇÃO DE BIOINSUMO A BASE Chlorella vulgaris SOBRE AS TROCAS GASOSAS E PRODUTIVIDADE DO SORGO - Cristina Sousa Barros de Oliveira, Débora; Pradi Vendruscolo, Eduardao; Luciana Queiroz Ribeiro , Brenda; Battistuzzi Martins , Murilo; Pacheco de Almeida Prado Bortolheiro , Fernanda (ANAIS DO ENIC, 2026)
-